GELİŞİMSEL BAKIŞ AÇISIYLA “WONDER” FİLMİNİN ANALİZİ - Üstündağ, Alev (Fırat University, 2021)
Araştırma “Wonder” (Mucize) filminin gelişimsel bakış açısıyla analiz edilmesi amacıyla yapılmıştır. Araştırmada nitel araştırma yöntemlerinden doküman analizi tekniği kullanılmıştır. Film, Çocuk Programlarına Yönelik İçerik Değerlendirme Formu kullanılarak analiz edilmiştir. Yapılan analiz sonucunda elde edilen bulgularının değerlendirilmesinde içerik analizi türlerinden frekans analizi kullanılmıştır. Filmde en fazla sosyal ve duygusal gelişim alanına yönelik içeriklerin bulunduğu belirlenmiştir. Sosyal ve duygusal gelişim alanına yönelik içerikleri sırasıyla bilişsel/algısal gelişim, model alma, aile yapısı, şiddet, psikomotor gelişim, aile değerleri ve cinsel gelişim alanına yönelik içerikler izlemiştir. Filmde genel anlamda dostluk, sevgi, yardımseverlik, sorumluluk, empati, özeleştiri içeriklerinin yoğun olduğu; bireysel farklılıklara saygı, kendini sevme, iyilik ve aile bağlarını güçlendirici mesajların verildiği, şiddet alanında olumsuz içeriklerin bulunmasının yanı sıra çoğunlukla iyi ve olumlu değerlerin çocuklara model olarak sunulduğu belirlenmiştir.

The research was conducted to analyze the Wonder movie from a developmental perspective. Document analysis technique, one of the qualitative research methods, was used in the research. The film was analyzed using the Content Evaluation Form for Children's Programs. Frequency analysis, one of the content analysis types, was used to evaluate the findings obtained as a result of the analysis. It has been determined that the content of the movie is mostly related to social and emotional development. The contents related to social and emotional development were followed by content regarding cognitive/perceptual development, modeling, family structure, violence, psychomotor development, family values, and sexual development, respectively. The content of the film is generally friendship, love, helpfulness, responsibility, empathy, and self-criticism; It has been determined that messages that strengthen individual differences, self-love, kindness, and family ties are given and that in addition to the negative content in the field of violence, mostly good and positive values are presented to children as a model.
Analysis of the Movie "Wonder" from a Developmental Perspective